Universities in Transition - Caldwell, Roger L.; Arizona Board of Regents, Phoenix ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
One of the working papers in the final report of the Arizona Board of Regents' Task Force on Excellence, Efficiency and Competitiveness, this document presents statistical data on the transition of Arizona's universities, consolidating many ad hoc analyses. It lists selected data that helped identify and develop Task Force issues and describes the transition of the universities over the past three decades. Institutional histories are presented for Northern Arizona University, Arizona State University, the University of Arizona, and Arizona community colleges. Faculty and student trends (e.g., overall enrollment changes, instructional distribution by colleges within the university, and distribution of degrees by subject area) are discussed. Research related data include sponsored projects listed by Arizona budget category and research activities by National Science Foundation categories. Budget distribution, capital construction, and program changes as indicators of university emphasis are noted. Data are summarized by such topics as external trends as indicators of internal shifts, degrees awarded as indicator of student interest, research funds received as indicator of research effort, and enrollment patterns as indicator of student trends. Ten conclusions include: Arizona's universities will probably continue in a transition state for the next decade; each university has a different mix of degrees awarded by type of degree; and research growth by the universities as a percentage of national research and development funds varies among the universities. Trend data tables are appended. (SM)
ERIC Note: In "The Arizona Board of Regents' Task Force on Excellence, Efficiency and Competitiveness. Final Report and Working Papers." Volume Two. For Volumes One and Two, see HE 022 446-447. For individual working papers, see HE 022 448-480 and HE 022 482-501. Some tables contain small print.
Educational level discussed: Higher Education.
Microfiche.
Keywords: Change; Change Strategies; Community Colleges; Competition; Educational Change; Educational Quality; Efficiency; Excellence in Education; Higher Education; Public Colleges; State Universities; Statewide Planning; Arizona; Arizona State University -- Arizona Task Force on Excellence Efficiency Compet -- Northern Arizona University -- University of Arizona; Reports, Descriptive; Numerical/Quantitative Data